Composite film and preparation method thereof, light-emitting device and preparation method thereof, and display panel
By combining metal oxides and organic compounds containing electronic transmission groups in the composite film, the problem of low electronic injection efficiency caused by metal oxides deep Lumo can be solved, and high -efficiency electronic injection and good film performance are achieved.
Patent Information
- Application Number
- CN202310927392.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-01-28
Smart Images

Figure CN119384156A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of display technology, and in particular to a composite film and a preparation method thereof, a light-emitting device and a preparation method thereof, and a display panel. Background Art
[0002] At present, when electron injection materials including metal oxides are used to prepare thin films, it is not conducive to achieving efficient electron injection because the metal oxides have a deep LUMO (Lowest Unoccupied Molecular Orbital) energy level. If the thin film is prepared by a solution method, although the method is simple, there is a problem of further reducing the electron injection efficiency. Summary of the invention
[0003] Based on this, the present application provides a composite film and a method for preparing the same, a light-emitting device and a method for preparing the same, and a display panel.
[0004] In a first aspect, a composite film is provided, characterized in that it comprises: a first film, wherein the first film comprises: a first functional material and a second functional material;
[0005] Wherein, the first functional material comprises: a metal oxide, and the second functional material comprises: an organic compound containing an electron transport group, wherein the electron transport group contains a lone pair of electrons;
[0006] The second functional material adsorbs the metal oxide or coordinates with metal ions in the metal oxide.
[0007] Optionally, the organic compound comprises a core and substituents attached to the core;
[0008] The parent core includes: one or more of the aromatic groups with 6 to 20 carbon atoms, the substituents include: one or more of the electron transporting groups, C1 to C5 alkyl groups, C1 to C5 alkoxy groups, substituted or unsubstituted nitrogen-containing heteroaryl groups with 5 to 20 ring atoms, and aromatic amino groups with 6 to 20 ring carbon atoms, and at least one of the substituents is the electron transporting group;
[0009] The substituent of the substituted nitrogen-containing heteroaryl is selected from C1-C5 alkyl, C1-C5 alkoxy, and aryl having 6 to 20 ring carbon atoms;
[0010] The electron transport group includes one or more of a pyridyl group, a quinolyl group, a triazine group, a pyrimidinyl group, an oxazolyl group, an oxadiazolyl group, a phenanthroline group and a benzimidazolyl group; or,
[0011] The mother core includes the electron transport group, the electron transport group is a substituted or unsubstituted phenanthroline group, and the substituent includes a C1-C5 alkyl group, a C1-C5 alkoxy group, an azacycloalkyl group having 2-6 carbon atoms, an aryl group having 6-20 ring carbon atoms, or an amino group substituted with a C1-C5 alkyl group;
[0012] The substituent of the substituted phenanthroline group is selected from one or more of a C1-C5 alkyl group, a C1-C5 alkoxy group, an aryl group having 6-20 carbon atoms, and an arylamino group having 6-20 carbon atoms;
[0013] And / or, the absolute value of LUMO of the organic compound is 2.0 to 3.5 eV.
[0014] Optionally, when the parent core includes one or more aromatic groups having 6 to 20 carbon atoms, the electron transport group is selected from one or more of the following structures:
[0015]
[0016] Here, * represents a connection site for connecting a substituent.
[0017] Optionally, when the mother core includes one or more aromatic groups having 6 to 20 carbon atoms, one of the connection sites of the electron transport group of formula (2) to formula (4) is connected to the mother core, and the other connection site is connected to -H.
[0018] Optionally, the mother core is selected from one or more of the following structures:
[0019] Among them, X m , X n , Y1, Y2 are substituents, m and n are independently selected from 1, 2 or 3;
[0020] X m , X n , Y1 and Y2, when each occurs, are independently selected from -H, C1-C5 alkyl, C1-C5 alkoxy, -NR 1 R 2 , an azacycloalkyl group having 2 to 6 carbon atoms, and an aryl group having 6 to 20 carbon atoms, one or more of R 1 and R 2 are independently selected from -H or C1-C5 alkyl; or
[0021] The mother core is selected from one or more of the following structures:
[0022]
[0023] Wherein, A1, A2, A3 are independently selected from N or CR 3 , R 3 is selected from -H or C1-C5 alkyl; Z p , Z q , Z s is a substituent, p is independently selected from 1, 2 or 3, q and s are independently selected from 1, 2, 3 or 4;
[0024] Z p , Z q , Z s Each occurrence is independently selected from *-Z o -Z t or *-Z t ;
[0025] Z o Each occurrence is selected from C1-C5 alkyl, C1-C5 alkoxy, aryl having 6 to 20 carbon atoms,
[0026] Z t Each occurrence is selected from C1-C5 alkyl, C1-C5 alkoxy or the electron transport group; and at least one Z t is the electron transport group; and / or
[0027] When the Z t When one or more of the electron transporting groups of formula (2) to (4) are selected, one of the connecting sites of the electron transporting group is connected to the parent core or -Z o The other linking site is linked to -H.
[0028] The second functional material is selected from one or more of the following structures:
[0029]
[0030] Optionally, the metal oxide includes: one or more of zinc oxide, tin oxide, magnesium-doped zinc oxide and lithium-doped zinc oxide;
[0031] and / or,
[0032] The mass ratio of the first functional material to the second functional material is (5:1) to (1:5).
[0033] Optionally, it further includes: a second film stacked with the first film, the absolute value of the LUMO energy level of the first film is 2.0 to 4.0 eV, and the absolute value of the LUMO energy level of the second film is 4.5 to 7.0 eV.
[0034] Optionally, the material of the second film includes one or more of: MoO3, ammonium molybdate, molybdenum ethoxide, phosphotungstic acid, phosphomolybdic acid, HATCN, NDP-9, F4TCNQ, F6TCNQ and CN6-CP; and / or,
[0035] The thickness of the first thin film and the second thin film are respectively 5-100 nm.
[0036] In a second aspect, a method for preparing the composite film according to the first aspect is provided, comprising:
[0037] providing a substrate;
[0038] Disposing a first solution on the substrate to form a first liquid film;
[0039] The first liquid film is subjected to a first annealing treatment to obtain a first thin film.
[0040] Optionally, the first solution includes an organic solvent, a first functional material and a second functional material,
[0041] The first functional material includes: a first solvent and a first film material; the first film material includes a second functional material and a metal oxide and / or a metal oxide precursor;
[0042] The metal oxide includes one or more of zinc oxide, tin oxide, magnesium-doped zinc oxide and lithium-doped zinc oxide, and the metal oxide precursor includes one or more of zinc acetylacetonate, zinc acetate, lithium acetylacetonate, lithium acetate, magnesium acetylacetonate and magnesium acetate.
[0043] Optionally, the first solvent includes: one or more of an alcohol solvent, an alcohol ether solvent or a ketone solvent;
[0044] and / or, the alcohol solvent is one or more of n-butanol, n-pentanol, n-hexanol, and cyclohexanol;
[0045] And / or, the alcohol ether solvent is one or more of ethylene glycol methyl ether, ethylene glycol dimethyl ether, ethylene glycol ethyl ether and ethylene glycol diethyl ether;
[0046] And / or, the ketone solvent is one or more of cyclohexanone and 3-pentanone;
[0047] And / or, the mass ratio of the first film material to the organic solvent is (1-10):(99-90).
[0048] Optionally, the temperature of the first annealing treatment is 100-200° C., and / or the time of the first annealing treatment is 5-60 min.
[0049] Optionally, a second solution is disposed on the first film to form a second liquid film;
[0050] The second liquid film is subjected to a second annealing treatment to obtain a second thin film.
[0051] Optionally, the temperature of the second annealing treatment is 100-200° C., and / or the time of the second annealing treatment is 5-60 min.
[0052] Optionally, the second solution includes a second solvent and a second film material;
[0053] The second thin film material comprises: one or more of MoO3, ammonium molybdate, molybdenum ethoxide, phosphotungstic acid, phosphomolybdic acid, HATCN, NDP-9, F4TCNQ, F6TCNQ and CN6-CP; and / or
[0054] The second solvent includes: one or more of an alcohol solvent, an alcohol ether solvent or a ketone solvent; and / or,
[0055] The alcohol solvent is one or more of n-butanol, n-pentanol, n-hexanol, and cyclohexanol; and / or,
[0056] The alcohol ether solvent is one or more of ethylene glycol methyl ether, ethylene glycol dimethyl ether, ethylene glycol ethyl ether and ethylene glycol diethyl ether; and / or,
[0057] The ketone solvent is one or more of cyclohexanone and 3-pentanone; and / or,
[0058] The mass ratio of the second film material to the second solvent is (1-10):(99-90).
[0059] In a third aspect, a light-emitting device is provided, comprising a first light-emitting unit, a composite film as described in the first aspect or a composite film prepared by the preparation method as described in the second aspect, and a second light-emitting unit which are stacked in sequence.
[0060] Optionally, the light emitting device further comprises: a first electrode layer and a second electrode layer;
[0061] The first light-emitting unit includes a first hole functional layer, a first light-emitting layer and a first electron functional layer;
[0062] The second light-emitting unit includes a second hole functional layer, a second light-emitting layer, and a second electron functional layer;
[0063] Wherein, from bottom to top, the first electrode layer, the first hole functional layer, the first light-emitting layer, the first electron functional layer, the composite film, the second hole functional layer, the second light-emitting layer, the second electron functional layer and the second electrode layer are stacked in sequence;
[0064] Optionally, the composite film further comprises a second film;
[0065] The first thin film is close to the first electron functional layer, and the second thin film of the composite thin film is close to the second hole functional layer.
[0066] Optionally, the materials of the first electrode layer and the second electrode layer are independently selected from one or more of metals, carbon materials and metal oxides, the metals include one or more of Al, Ag, Cu, Mo, Au, Ba, and Mg; the carbon materials include one or more of graphite, carbon nanotubes, graphene and carbon fibers; the metal oxides include doped or undoped metal oxides, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or include a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2;
[0067] And / or, the materials of the first hole functional layer and the second hole functional layer are independently selected from TFB (poly [(9,9-dioctylfluorene-2,7-diyl)-co-(4,4′-(N-(4-sec-butylphenyl)diphenylamine)]), PVK (poly (9-vinylcarbazole)), poly-TPD (poly [bis (4-phenyl) (4-butylphenyl) amine]), poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, 2,3,5,6-tetrafluoro-7, One or more of 7',8,8'-tetracyanoquinone-dimethane, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, copper phthalocyanine, transition metal oxides and transition metal sulfide compounds, wherein the transition metal oxide is selected from one or more of NiO, MoO2, WO3 and CuO, and the metal sulfide compound is selected from one or more of MoS2, MoSe2, WS3, WSe3, CuS and CuSCN;
[0068] And / or, the materials of the first light-emitting layer and the second light-emitting layer are independently selected from organic light-emitting materials or quantum dot light-emitting materials; the organic light-emitting materials include: at least one of carbazole derivatives, triazine derivatives, oxazole derivatives, iridium-containing phosphorescent materials and platinum-containing phosphorescent materials; the quantum dot light-emitting materials are selected from at least one of single-structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, the single-structure quantum dots are selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds, the II-VI compounds are selected from CdS, CdSe, CdTe, ZnS , ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, C At least one of dHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe The IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe, and the III-V group compound is selected from at least one of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, and GaPSb , at least one of AlNPs, AlNAs, AlNSb, AlPAs, AlPSb, InNPs, InNAs, InNSb, InPAs, InPSb, GaAlNPs, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNPs, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNPs, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2;The core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, organic perovskite semiconductors or organic-inorganic hybrid perovskite semiconductors; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2 + , Yb 2+ and Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic perovskite semiconductor is CMX3, wherein C is a carboxamidine group, M is a divalent metal cation, and M is selected from b 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ and Eu 2+ At least one of, X is a halogen anion selected from Cl-, Br - or at least one of I-; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH 3+ or [NH3(CH2) n NH3] 2+ , wherein n≥2, M is a divalent metal cation selected from b 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ and Eu 2+ At least one of, X is a halogen anion selected from Cl-, Br - ,I - At least one of;
[0069] And / or, the first electronic functional layer and the second electronic functional layer include an electron injection layer and / or an electron transport layer, and the materials of the electron injection layer and the electron transport layer are independently selected from one or more of doped or undoped inorganic materials and organic materials; wherein the undoped inorganic material is selected from one or more of ZnO, TiO2, SnO2, Al2O3, GaO, Ga2O3, ZrO2, ZnS, ZnSe, CdS, BaTiO3, Cs2CO3 and Rb2CO3; the doped inorganic material includes the undoped inorganic material and a doping element, and the doping element is selected from one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti and Y; the organic material contained in the electron transport layer is selected from one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds and hydroxyquinoline compounds.
[0070] In a fourth aspect, a display panel is provided, comprising the light emitting device as described in the third aspect.
[0071] Compared with the prior art, this application has the following beneficial effects:
[0072] The composite film includes a first functional material and a second functional material. The metal oxide is combined with the group containing lone pair electrons in the second functional material through adsorption or coordination, which can effectively reduce the electron affinity, that is, reduce the electron injection barrier. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] Figure 1 A schematic diagram of a cross-sectional structure of a composite film provided in an embodiment of the present application;
[0074] Figure 2 A schematic cross-sectional structure diagram of a light emitting device provided in an embodiment of the present application. DETAILED DESCRIPTION
[0075] The present application is further described in detail below in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the present application disclosure more thorough and comprehensive.
[0076] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0077] Light-emitting diodes prepared based on the solution method (such as organic light-emitting diodes (OLED)) are suitable for low-cost manufacturing processes and have outstanding advantages in large-area and rich-shaped terminal display screens. Therefore, they are still a hot topic for research by different researchers.
[0078] However, compared with inorganic light-emitting diode (LED) devices, OLEDs prepared based on the solution method have a shorter lifespan. Therefore, when designing the device, two OLEDs can be connected in series (stacked device) to reduce the current density required for the device at the same brightness, thereby increasing the device's lifespan. This is also an important direction for improving the current lifespan of OLEDs.
[0079] In a stacked device, the cathode and anode connected between multiple light-emitting units are usually replaced by a charge generation layer. The current mainstream charge generation layer is composed of a doped PN heterojunction or an undoped accumulation-type heterojunction. This is relatively easy to achieve for the evaporation process, but in the solution method preparation process, it is necessary to consider the destruction of the completed film, the screening of doping materials that are stable in the solution, and high-temperature annealing treatment. This makes the development of solution-based stacked devices more difficult.
[0080] Especially for electron injection materials containing metal oxides, when they are used to prepare composite thin films, since the metal oxides have a deeper LUMO (Lowest Unoccupied Molecular Orbital) energy level, it is not conducive to the efficient electron injection of the composite thin film; for example, the absolute value of the LUMO energy level of ZnO is about 4eV, and there is still a large injection barrier between it and the absolute value of the LUMO energy level of the electron transport layer or the light-emitting layer (less than 3eV). Therefore, when metal oxides such as ZnO are used to prepare composite thin films, it is not conducive to the efficient injection of electrons into the electron transport layer or the light-emitting layer.
[0081] In particular, in the related art, a solution method is usually adopted to prepare the composite film. Although the composite film obtained in this way is easy to prepare, it has the problem of further reducing the electron injection efficiency.
[0082] Based on the above technical problems, in the first aspect, some embodiments of the present application provide a composite film, such as Figure 1 and Figure 2 As shown, it comprises: a first film 1, the first film 1 comprises: a first functional material and a second functional material;
[0083] Wherein, the first functional material comprises: a metal oxide, and the second functional material comprises: an organic compound containing an electron transport group, wherein the electron transport group contains a lone pair of electrons;
[0084] The second functional material adsorbs the metal oxide or coordinates with the metal ions in the metal oxide.
[0085] In the composite film provided in the embodiment of the present application, the composite film includes a first functional material and a second functional material, the first functional material includes: a metal oxide, the second functional material includes: an organic compound containing an electron transport group, the electron transport group contains a lone pair of electrons; the second functional material adsorbs the metal oxide or coordinates with the metal ions in the metal oxide, so, on the one hand, the metal oxide can be combined with the electron transport group in the second functional material by adsorption or coordination, which can effectively reduce the electron affinity, that is, it can reduce the electron injection barrier to the electron transport layer or the light-emitting layer, so that the electrons generated by the composite film prepared by the material can be injected into the electron transport layer or the light-emitting layer at a low voltage. On the other hand, the first functional material and the second functional material are inorganic-organic composite materials, which can form a complex, and the complex has good stability in the solution, so the composite film is very suitable for solution preparation.
[0086] In some embodiments, the organic compound comprises a core and substituents attached to the core;
[0087] The parent core includes: one or more of an aromatic group having 6 to 20 carbon atoms, and the substituent includes: one or more of an electron transport group, a C1 to C5 alkyl group, a C1 to C5 alkoxy group, a substituted or unsubstituted nitrogen-containing heteroaryl group having 5 to 20 ring atoms, and an aromatic amino group having 6 to 20 ring carbon atoms, and at least one of the substituents is an electron transport group;
[0088] The substituent of the substituted nitrogen-containing heteroaryl is selected from C1-C5 alkyl, C1-C5 alkoxy, and aryl having 6 to 20 ring carbon atoms;
[0089] The electron transport group includes one or more of a pyridyl group, a quinolyl group, a triazine group, a pyrimidinyl group, an oxazolyl group, an oxadiazolyl group, a phenanthroline group and a benzimidazolyl group;
[0090] Alternatively, the mother core includes an electron transport group, the electron transport group is a substituted or unsubstituted phenanthroline group, and the substituent includes a C1-C5 alkyl group, a C1-C5 alkoxy group, an azacycloalkyl group having 2-6 carbon atoms, an aryl group having 6-20 ring carbon atoms, or an amino group substituted with a C1-C5 alkyl group;
[0091] The substituent of the substituted phenanthroline group is selected from one or more of a C1-C5 alkyl group, a C1-C5 alkoxy group, an aryl group having 6-20 carbon atoms, and an arylamino group having 6-20 carbon atoms.
[0092] In these embodiments, when the parent core includes: one or more of aromatic groups having 6 to 20 carbon atoms, the substituents include: one or more of electron transport groups, C1 to C5 alkyl groups, C1 to C5 alkoxy groups, substituted or unsubstituted nitrogen-containing heteroaryl groups having 5 to 20 ring atoms, and aromatic amino groups having 6 to 20 ring carbon atoms, and at least one substituent is an electron transport group, the electron transport group acts as an end group to adsorb metal oxides or coordinate with metal ions in the metal oxide, and the surrounding steric hindrance of the electron transport group is small, thereby maintaining good coordination ability.
[0093] When the parent core includes an electron transport group, the electron transport group is a substituted or unsubstituted phenanthroline group, and the substituent includes a C1-C5 alkyl group, a C1-C5 alkoxy group, an azacycloalkyl group having 2 to 6 carbon atoms, an aryl group having 6 to 20 ring carbon atoms, or an amino group substituted with a C1-C5 alkyl group, the phenanthroline group acts as an electron transport group and simultaneously plays a role in adsorbing metal oxides or coordinating with metal ions in metal oxides.
[0094] In some embodiments, the absolute value of the LUMO energy level of the organic compound is 2.0 to 3.5 eV.
[0095] These organic compounds have a shallow energy level, which can effectively reduce the electron injection barrier between them and the absolute value of the LUMO energy level (less than 3 eV) of the electron transport layer or the light-emitting layer.
[0096] In some embodiments, when the parent core includes one or more aromatic groups having 6 to 20 carbon atoms, the electron transport group is selected from one or more of the following structures:
[0097]
[0098] Here, * represents a connection site for connecting a substituent.
[0099] In these embodiments, the electron transport group is one or more of a pyridyl group, a quinolyl group, a bipyridyl group, and a phenanthroline group.
[0100] In some embodiments, when the parent core includes one or more aromatic groups having 6 to 20 carbon atoms, one of the connection sites of the electron transport groups of Formula (2) to (4) is connected to the parent core, and the other connection site is connected to -H.
[0101] In other embodiments, the mother core is selected from one or more of the following structures:
[0102]
[0103] Among them, X m , X n , Y1, Y2 are substituents, m and n are independently selected from 1, 2 or 3;
[0104] X m , X n , Y1 and Y2, when each occurs, are independently selected from -H, C1-C5 alkyl, C1-C5 alkoxy, -NR 1 R 2 , an azacycloalkyl group having 2 to 6 carbon atoms, and an aryl group having 6 to 20 carbon atoms, one or more of R 1 and R 2 are independently selected from -H or C1-C5 alkyl; or
[0105] The mother core is selected from one or more of the following structures:
[0106]
[0107] Wherein, A1, A2, A3 are independently selected from N or CR 3 , R 3 is selected from -H or C1-C5 alkyl; Z p , Z q , Z s is a substituent, p is independently selected from 1, 2 or 3, q and s are independently selected from 1, 2, 3 or 4;
[0108] Z p , Z q , Z s Each occurrence is independently selected from *-Z o -Z t or *-Z t ;
[0109] Z o Each occurrence is selected from C1-C5 alkyl, C1-C5 alkoxy, aryl having 6 to 20 carbon atoms,
[0110] Z tEach occurrence is selected from C1-C5 alkyl, C1-C5 alkoxy or the electron transport group; and at least one Z t is an electron transport group; when Z t When one or more of the electron transporting groups of formula (2) to (4) are selected, one of the connecting sites of the electron transporting group is connected to the parent core or -Z o The other linking site is linked to -H.
[0111] In some examples, the second functional material is selected from one or more of the following structures:
[0112]
[0113]
[0114] The structures shown in (a) to (l) above and their corresponding names can be shown as follows:
[0115]
[0116] In some embodiments, the metal oxide includes one or more of zinc oxide, tin oxide, magnesium-doped zinc oxide, and lithium-doped zinc oxide.
[0117] Among them, metal ions such as Zn ions in the above-mentioned metal oxides can be combined with groups containing lone pair electrons through adsorption or coordination, which can effectively reduce the electron affinity of ZnO, that is, reduce the electron injection barrier of ZnO into the electron transport layer or the light-emitting layer.
[0118] At the same time, the first functional material and the second functional material are inorganic-organic composite materials and can form a complex. The complex has good stability in the solution. Therefore, the composite film is very suitable for solution method preparation.
[0119] In some embodiments, the mass ratio of the first functional material to the second functional material is (5:1) to (1:5).
[0120] In these embodiments, the electron efficient injection can be effectively reduced.
[0121] In some optional embodiments, the mass ratio of the first functional material to the second functional material is (2:1) to (1:2).
[0122] Among them, the above-mentioned composite film 10 example may include a charge generating layer, and the first film 1 may serve as an n-type layer in the heterojunction of the charge generating layer for electron transport and injection, or, the first film 1 may be arranged on the charge generating interface of the charge generating layer to transport and inject electrons, so as to facilitate charge separation and electron injection at the charge generating interface at a lower driving voltage.
[0123] In some embodiments, Figure 1 and Figure 2 As shown, the composite film 10 further includes: a second film 2 stacked with the first film 1, the absolute value of the LUMO energy level of the first film 1 is 2.0-4.0 eV, and the absolute value of the LUMO energy level of the second film 2 is 4.5-7.0 eV.
[0124] In these embodiments, the second film 2 can make the electrons generated by the charge generation interface 101 more efficiently injected into the second film 2, realize effective charge separation, and improve the charge separation efficiency. The first film 1 has a shallower LUMO energy level, which can reduce the injection barrier between it and the LUMO energy level of the electron transport layer or the light-emitting layer, thereby making the electrons more efficiently injected into the electron transport layer or the light-emitting layer.
[0125] Specifically, the material of the second film 2 can be any material that can inject the electrons generated by the charge generation interface 101 into the second film 2 through tunneling.
[0126] Here, it should be noted that at the charge generation interface 101, if holes and electrons can move to the hole transport layer and the electron transport layer respectively to reduce recombination, the separation ability of holes and electrons will be better. If the probability of holes and electrons moving to the hole transport layer and the electron transport layer respectively is small and recombination occurs between the two, the separation ability of holes and electrons will be poor.
[0127] In order to reduce the recombination of holes and electrons and improve the separation ability of holes and electrons, in the embodiment of the present application, the second film 2 may include: a dopant of a p-type material. In this way, the second film 2 can act as an electron acceptor to attract electrons in the hole transport layer to tunnel into the second film 2, thereby achieving efficient electron injection, which is manifested microscopically as follows: electrons in the valence band (HOMO energy level) of the hole transport layer tunnel to the LUMO energy level in the second film 2, and the hole transport layer that loses electrons continuously forms holes in the valence band, thereby achieving separation of holes and electrons.
[0128] In addition, it should be noted that this type of material usually has a deeper LUMO energy level (absolute value greater than or equal to 5eV). Before the first film 1 is set, there is a certain injection barrier between the second film 2 and the electron transport layer or the light-emitting layer (the absolute value of the LUMO energy level is less than 3eV). After the first film 1 with a lower electron injection barrier is set between it and the electron transport layer or the light-emitting layer, electrons can be exchanged between the first film 1 and the second film 2 without forming a restrictive electron transport barrier, thereby improving the efficient electron injection and reducing the driving voltage.
[0129] In addition, the adsorption or coordination between the second functional material and the metal ions in the above-mentioned first film 1 can further reduce the electron affinity of the metal oxide, thereby further reducing the electron injection barrier of the first film 1 to the electron transport layer or the light-emitting layer, playing a role in assisting electron injection, and can inject the electrons generated by the charge generation layer into the light-emitting layer at a low voltage.
[0130] In some embodiments, the material of the second film 2 includes one or more of: MoO3 nanoparticles, ammonium molybdate, molybdenum ethoxide, phosphotungstic acid, phosphomolybdic acid, HATCN, NDP-9, F4TCNQ, F6TCNQ and CN6-CP.
[0131] In some embodiments, the thickness of the first film 1 and the second film 2 are both 5-100 nm.
[0132] In a second aspect, some embodiments of the present application provide a method for preparing a composite film as described in the first aspect, comprising:
[0133] providing a substrate;
[0134] Disposing a first solution on the substrate to form a first liquid film;
[0135] The first liquid film is subjected to a first annealing treatment to obtain a first thin film.
[0136] In some embodiments, the first solution includes a first solvent and a first thin film material, and the first thin film material includes: a metal oxide and / or a metal oxide precursor;
[0137] The metal oxides include one or more of zinc oxide, tin oxide, magnesium-doped zinc oxide and lithium-doped zinc oxide, and the metal oxide precursors include one or more of zinc acetylacetonate, zinc acetate, lithium acetylacetonate, lithium acetate, magnesium acetylacetonate and magnesium acetate.
[0138] In some embodiments, the first solvent includes: one or more of an alcohol solvent, an alcohol ether solvent, or a ketone solvent;
[0139] and / or, the alcohol solvent is one or more of n-butanol, n-pentanol, n-hexanol, and cyclohexanol;
[0140] and / or, the alcohol ether solvent is one or more of ethylene glycol methyl ether, ethylene glycol dimethyl ether, ethylene glycol ethyl ether and ethylene glycol diethyl ether;
[0141] and / or, the ketone solvent is one or more of cyclohexanone and 3-pentanone;
[0142] And / or, the mass ratio of the first functional material and / or the second functional material to the organic solvent is (1-10):(99-90).
[0143] By mixing the first functional material and the second functional material with an organic solvent to prepare a first solution, a first thin film can be prepared by a solution method, and the first thin film finally formed has a high electron injection efficiency.
[0144] In some embodiments, the temperature of the first annealing treatment is 100-200° C., and / or the time of the first annealing treatment is 5-60 minutes.
[0145] In some embodiments, a second solution is disposed on the first film to form a second liquid film;
[0146] The second liquid film is subjected to a second annealing treatment to obtain a second thin film.
[0147] In some embodiments, the temperature of the second annealing treatment is 100-200° C., and / or the time of the second annealing treatment is 5-60 minutes.
[0148] In some embodiments, the second solution includes a second solvent and a second film material;
[0149] The second thin film material comprises: one or more of MoO3, ammonium molybdate, molybdenum ethoxide, phosphotungstic acid, phosphomolybdic acid, HATCN, NDP-9, F4TCNQ, F6TCNQ and CN6-CP; and / or
[0150] The second solvent includes: one or more of an alcohol solvent, an alcohol ether solvent or a ketone solvent; and / or,
[0151] The alcohol solvent is one or more of n-butanol, n-pentanol, n-hexanol, and cyclohexanol; and / or,
[0152] The alcohol ether solvent is one or more of ethylene glycol methyl ether, ethylene glycol dimethyl ether, ethylene glycol ethyl ether and ethylene glycol diethyl ether; and / or,
[0153] The ketone solvent is one or more of cyclohexanone and 3-pentanone; and / or,
[0154] The mass ratio of the second film material to the second solvent is (1-10):(99-90).
[0155] In a third aspect, some embodiments of the present application provide a light emitting device 100, such as Figure 2 As shown, the light-emitting device 100 includes a first light-emitting unit, a composite film 10 as described in the first aspect or a composite film 10 prepared by the preparation method as described in the second aspect, and a second light-emitting unit which are sequentially stacked.
[0156] In some embodiments, the light emitting device 100 further includes: a first electrode layer 20 and a second electrode layer 30;
[0157] The first light-emitting unit 40A includes a first hole functional layer 3, a first light-emitting layer 4 and a first electron functional layer 5;
[0158] The second light-emitting unit 40B includes a second hole functional layer 7, a second light-emitting layer 8 and a second electron functional layer 9;
[0159] Among them, along the direction from bottom to top, the first electrode layer 20, the first hole functional layer 3, the first light-emitting layer 4, the first electron functional layer 5, the composite film 10, the second hole functional layer 6, the second light-emitting layer 7, the second electron functional layer 8 and the second electrode layer 30 are stacked in sequence.
[0160] In some embodiments, the composite film 10 further includes a second film 2;
[0161] The first film 1 is close to the first electronic functional layer 5 , and the second film 2 of the composite film 10 is close to the second hole functional layer 6 .
[0162] In these embodiments, the interface between the second hole functional layer 6 and the second film 2 can constitute a charge generation interface 101. In this way, under the drive of voltage, the electrons at the charge generation interface 101 are transmitted to the second film 2 by tunneling. There is a smaller electron injection barrier between the second film 2 and the first film 1. The electrons in the second film 2 are transmitted to the first film 1 by overcoming the electron injection barrier. The electrons in the first film 1 can then overcome the electron injection barrier between the first film 1 and the first electron functional layer 5, and the electrons generated by the charge generation layer can be injected into the light-emitting layer (that is, the first light-emitting layer 4) in the first light-emitting unit 40A at a lower voltage.
[0163] In some embodiments, the materials of the first electrode layer 20 and the second electrode layer 30 are independently selected from one or more of metals, carbon materials and metal oxides, wherein the metals include one or more of Al, Ag, Cu, Mo, Au, Ba and Mg; the carbon materials include one or more of graphite, carbon nanotubes, graphene and carbon fibers; the metal oxides include doped or undoped metal oxides, including ITO (Indium Tin Oxide), FTO (F-doped Tin Oxide), ATO (Antimony Doped Tin Oxide), AZO (Al-doped Zinc Oxide), GZO (Gallium doped Zinc Oxide), IZO (Indium-Zinc-Oxide), MZO (Mg-doped Zinc Oxide) and AMO (Active Magnesium Doped Zinc Oxide). Oxide, active magnesium oxide), or a composite electrode comprising a metal sandwiched between doped or undoped transparent metal oxides, wherein the composite electrode comprises one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2;
[0164] And / or, the materials of the first hole functional layer and the second hole functional layer are independently selected from TFB (poly [(9,9-dioctylfluorene-2,7-diyl)-co-(4,4′-(N-(4-sec-butylphenyl)diphenylamine)]), PVK (poly (9-vinylcarbazole)), poly-TPD (poly [bis (4-phenyl) (4-butylphenyl) amine]), poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, 2,3,5,6-tetrafluoro-7, One or more of 7',8,8'-tetracyanoquinone-dimethane, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, copper phthalocyanine, transition metal oxides and transition metal sulfide compounds, wherein the transition metal oxide is selected from one or more of NiO, MoO2, WO3 and CuO, and the metal sulfide compound is selected from one or more of MoS2, MoSe2, WS3, WSe3, CuS and CuSCN;
[0165] And / or, the materials of the first light-emitting layer and the second light-emitting layer are independently selected from organic light-emitting materials or quantum dot light-emitting materials; the organic light-emitting materials include: at least one of carbazole derivatives, triazine derivatives, oxazole derivatives, iridium-containing phosphorescent materials and platinum-containing phosphorescent materials; the quantum dot light-emitting materials are selected from at least one of single-structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, the single-structure quantum dots are selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds, the II-VI compounds are selected from CdS, CdSe, CdTe, ZnS , ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, C At least one of dHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe The IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe, and the III-V group compound is selected from at least one of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, and GaPSb , at least one of AlNPs, AlNAs, AlNSb, AlPAs, AlPSb, InNPs, InNAs, InNSb, InPAs, InPSb, GaAlNPs, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNPs, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNPs, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2;The core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, organic perovskite semiconductors or organic-inorganic hybrid perovskite semiconductors; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2 + , Yb 2+ and Eu 2+ At least one of, X is a halogen anion selected from Cl-, Br - , I- at least one; the general structural formula of the organic perovskite semiconductor is CMX3, wherein C is a carboxamidine group, M is a divalent metal cation, and M is selected from b 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ and Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - or I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH 3+ or [NH3(CH2) n NH3] 2+ , wherein n≥2, M is a divalent metal cation selected from b 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ and Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - , at least one of I-;
[0166] And / or, the materials of the first electronic functional layer and the second electronic functional layer are independently selected from one or more of doped or undoped inorganic materials and organic materials; wherein the undoped inorganic material is selected from one or more of ZnO, TiO2, SnO2, Al2O3, GaO, Ga2O3, ZrO2, ZnS, ZnSe, CdS, BaTiO3, Cs2CO3 and Rb2CO3; the doped inorganic material includes the undoped inorganic material and doping elements, and the doping elements are selected from one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti and Y; the organic material contained in the electron transport layer is selected from one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds and hydroxyquinoline compounds.
[0167] In some embodiments, the first electron functional layer, the second electron functional layer, the first hole functional layer and the second hole functional layer can independently be one layer or more layers, which is not specifically limited here.
[0168] Multi-layer here refers to two layers or more.
[0169] Only the case of two stacked light-emitting units 40 is listed here. It should be noted that the light-emitting device 100 may also include three or more light-emitting units 40. The above-mentioned composite film 10 may be arranged between two adjacent light-emitting units 40. The specific stacking sequence and electron injection and transmission paths can refer to the examples of the first light-emitting unit 40A, the composite film 10 and the second light-emitting unit 40B, which will not be repeated here.
[0170] In a fourth aspect, some embodiments of the present application provide a method for preparing a light-emitting device, comprising:
[0171] Providing a light-emitting device preform, wherein the light-emitting device preform comprises a first electrode layer and a first light-emitting unit which are sequentially stacked;
[0172] Preparing the composite film as described in the third aspect on the first light-emitting unit;
[0173] The second light-emitting unit is sequentially prepared on the composite film.
[0174] In some embodiments, the step of preparing the composite film on the first light-emitting unit includes:
[0175] Disposing composite material ink on the first light-emitting unit to form a first film;
[0176] A solution containing a material for a second thin film is disposed on the first thin film to form the second thin film.
[0177] In some embodiments, the composite material ink is disposed on the first light-emitting unit and the solution containing the material of the second film is disposed on the first film can be disposed by one or more of spin coating, scraper coating, spray coating, screen printing, and inkjet printing.
[0178] Some embodiments of the present application provide a display panel, including the light-emitting device as described above, or the light-emitting device prepared by the method as described above. The display panel can be any electronic product with a display function, and the electronic product includes but is not limited to a smart phone, a tablet computer, a laptop computer, a digital camera, a digital video camera, a smart wearable device, a smart weighing electronic scale, a car display, a television or an e-book reader, wherein the smart wearable device can be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.
[0179] In the following examples and comparative examples, all raw materials can be purchased in commercial form, and in order to maintain the reliability of the experiment, the raw materials used in the following examples and comparative examples have the same physical and chemical parameters or are processed in the same way.
[0180] Example 1
[0181] The preparation method of the light emitting device in Example 1 is as follows:
[0182] Step 1), the ITO anode substrate is cleaned and then treated under UV conditions for 15 minutes to increase its work function and wettability.
[0183] Step 2), on the treated ITO anode substrate, spin-coat 30nm thick PEDOT:PSS and bake it at 150℃ in air atmosphere for 20min; then spin-coat TFB as a hole transport layer on the PEDOT:PSS substrate with a thickness of 30nm, and then bake it at 180℃ in nitrogen environment for 60min.
[0184] Step 3), spin-coat a 60 nm thick polymer light-emitting layer F8BT on the substrate with the hole transport layer formed thereon, and bake at 150° C. for 10 min.
[0185] Step 4), spin-coat a n-butanol solution of ZnO nanoparticles and p-Pyrrd-Phen on the light-emitting layer, and anneal at 150° C. for 20 min to prepare a 20 nm thick first film, wherein the ZnO nanoparticles have a particle size of 8 nm, and the mass ratio of ZnO nanoparticles to p-Pyrrd-Phen is 2:1.
[0186] Step 5), spin coating an ethanol molybdenum solution on the first film and annealing at 120° C. for 20 min to obtain a second film with a thickness of 10 nm; wherein the solvents in the ethanol molybdenum solution are ethanol and methanol, and the volume ratio of ethanol to methanol is 1:1.
[0187] Step 6), spin-coat TFB as a hole transport layer on the second film with a thickness of 30 nm, and bake at 180° C. for 60 min.
[0188] Step 7), a 60 nm thick polymer light-emitting layer F8BT was spin-coated on the hole transport layer prepared in step 6), and baked at 150° C. for 10 min.
[0189] Step 8), vacuum evaporate 1 nm of LiF and 100 nm of Al on the light-emitting layer prepared in step 7), finally package and anneal at 80° C. for 30 min to obtain a light-emitting device.
[0190] Example 2
[0191] The method for preparing the light-emitting device in Example 2 is substantially the same as the method for preparing the light-emitting device in Example 1, except that in step 4), the mass ratio of ZnO nanoparticles to p-Pyrrd-Phen is 4.5:1.
[0192] Example 3
[0193] The method for preparing the light-emitting device in Example 3 is substantially the same as the method for preparing the light-emitting device in Example 1, except that in step 4), the mass ratio of ZnO nanoparticles to p-Pyrrd-Phen is 1:4.5.
[0194] Example 4
[0195] The method for preparing the light-emitting device in Example 4 is substantially the same as the method for preparing the light-emitting device in Example 1, except that in step 4), the mass ratio of ZnO nanoparticles to p-Pyrrd-Phen is 6:1.
[0196] Example 5
[0197] The method for preparing the light-emitting device in Example 5 is substantially the same as the method for preparing the light-emitting device in Example 1, except that in step 4), the mass ratio of ZnO nanoparticles to p-Pyrrd-Phen is 1:6.
[0198] Example 6
[0199] The method for preparing the light-emitting device in Example 6 is substantially the same as the method for preparing the light-emitting device in Example 1, except that in step 4), the mass ratio of ZnO nanoparticles to p-Pyrrd-Phen is 5:1.
[0200] Example 7
[0201] The method for preparing the light-emitting device in Example 7 is substantially the same as the method for preparing the light-emitting device in Example 1, except that in step 4), the mass ratio of ZnO nanoparticles to p-Pyrrd-Phen is 1:5.
[0202] Example 8
[0203] The method for preparing the light-emitting device in Example 8 is substantially the same as the method for preparing the light-emitting device in Example 1, except that: B4PYPPyPM is used to replace p-Pyrrd-Phen in step 4).
[0204] Example 9
[0205] The method for preparing the light-emitting device in Example 9 is substantially the same as the method for preparing the light-emitting device in Example 1, except that: Bpy-FOXD is used to replace p-Pyrrd-Phen in step 4).
[0206] Comparative Example 1
[0207] The preparation method of the light-emitting device in Comparative Example 1 is substantially the same as that in Example 1, except that in step 4), the electron auxiliary injection layer only contains ZnO nanoparticles but does not contain p-Pyrrd-Phen.
[0208] Comparative Example 2
[0209] The preparation method of the light-emitting device in Comparative Example 2 is substantially the same as that in Example 1, except that in step 4), the electron auxiliary injection layer only contains p-Pyrrd-Phen but does not contain ZnO nanoparticles.
[0210] Comparative Example 3
[0211] The preparation method of the light-emitting device in Comparative Example 3 is substantially the same as that in Example 1, except that: in step 4), BTB (the structure is shown below) is used to replace p-Pyrrd-Phen.
[0212]
[0213] The device performance of the devices prepared in the above-mentioned embodiments and comparative examples was tested using IVL equipment, and the device life was measured using life aging equipment. The results are shown in Table 1 below.
[0214] Table 1
[0215]
[0216]
[0217] It can be seen from Table 1 that when the current density is 10 mA / cm 2 The voltage at (J10) is used as the driving voltage index, the current efficiency at a brightness of 1000nit is used as the efficiency index, and the time when the brightness decays to 95% under constant current conditions from an initial brightness of 1000nit is used as the life evaluation index. By comparing Examples 1 to 9 with Comparative Examples 1 to 3, it can be seen that the device can have better performance by compounding the first functional material and the second functional material; by comparing Examples 1 to 3, Examples 6 to 7 with Examples 4 to 5, it can be seen that by controlling the ratio of the first functional material and the second functional material, the charge generation unit can efficiently inject the charge generated by the charge generation layer into the light-emitting layers on both sides, and the device performance is better.
[0218] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0219] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A composite film, characterized in that: include: A first film, the first film comprising: a first functional material and a second functional material; Wherein, the first functional material comprises: a metal oxide, and the second functional material comprises: an organic compound containing an electron transport group, wherein the electron transport group contains a lone pair of electrons; The second functional material adsorbs the metal oxide or coordinates with metal ions in the metal oxide.
2. The composite film according to claim 1, characterized in that The organic compound comprises a parent core and a substituent attached to the parent core; The parent core includes: one or more of the aromatic groups with 6 to 20 carbon atoms, the substituents include: one or more of the electron transporting groups, C1 to C5 alkyl groups, C1 to C5 alkoxy groups, substituted or unsubstituted nitrogen-containing heteroaryl groups with 5 to 20 ring atoms, and aromatic amino groups with 6 to 20 ring carbon atoms, and at least one of the substituents is the electron transporting group; The substituent of the substituted nitrogen-containing heteroaryl is selected from C1-C5 alkyl, C1-C5 alkoxy, and aryl having 6 to 20 ring carbon atoms; The electron transport group includes one or more of a pyridyl group, a quinolyl group, a triazine group, a pyrimidinyl group, an oxazolyl group, an oxadiazolyl group, a phenanthroline group and a benzimidazolyl group; or, The mother core includes the electron transport group, the electron transport group is a substituted or unsubstituted phenanthroline group, and the substituent includes a C1-C5 alkyl group, a C1-C5 alkoxy group, an azacycloalkyl group having 2-6 carbon atoms, an aryl group having 6-20 ring carbon atoms, or an amino group substituted with a C1-C5 alkyl group; The substituent of the substituted phenanthroline group is selected from one or more of a C1-C5 alkyl group, a C1-C5 alkoxy group, an aryl group having 6-20 carbon atoms, and an arylamino group having 6-20 carbon atoms; And / or, the absolute value of the LUMO energy level of the organic compound is 2.0 to 3.5 eV.
3. The composite film according to claim 2, characterized in that: When the parent core includes one or more aromatic groups having 6 to 20 carbon atoms, the electron transport group is selected from one or more of the following structures: Here, * represents a connection site for connecting a substituent.
4. The composite film according to claim 3, characterized in that: One of the connection sites of the electron transport groups of formula (2) to formula (4) is connected to the mother core, and the other connection site is connected to -H.
5. The composite film according to claim 3, characterized in that: The mother core is selected from one or more of the following structures: Among them, X m , X n , Y1, Y2 are substituents, m and n are independently selected from 1, 2 or 3; X m , X n , Y1 and Y2, when each occurs, are independently selected from -H, C1-C5 alkyl, C1-C5 alkoxy, -NR 1 R 2 , an azacycloalkyl group having 2 to 6 carbon atoms, and an aryl group having 6 to 20 carbon atoms, one or more of R 1 and R 2 are independently selected from -H or C1-C5 alkyl; or The mother core is selected from one or more of the following structures: Wherein, A1, A2, A3 are independently selected from N or CR 3 , R 3 is selected from -H or C1-C5 alkyl; Z p , Z q , Z s is a substituent, p is independently selected from 1, 2 or 3, q and s are independently selected from 1, 2, 3 or 4; Z p , Z q , Z s Each occurrence is independently selected from *-Z o -Z t or *-Z t ; Z o Each occurrence is selected from C1-C5 alkyl, C1-C5 alkoxy, aryl having 6 to 20 carbon atoms, Z t Each occurrence is selected from C1-C5 alkyl, C1-C5 alkoxy or the electron transport group; and at least one Z t is the electron transport group; and / or, When the Z t When one or more of the electron transporting groups of formula (2) to (4) are selected, one of the connecting sites of the electron transporting group is connected to the parent core or -Z o The other linking site is linked to -H.
6. The composite film according to claim 5, characterized in that: The second functional material is selected from one or more of the following structures:
7. The composite film according to claim 1, characterized in that The metal oxide comprises: one or more of zinc oxide, tin oxide, magnesium-doped zinc oxide and lithium-doped zinc oxide; and / or, The mass ratio of the first functional material to the second functional material is (5:1) to (1:5).
8. The composite film according to any one of claims 1 to 7, characterized in that: Also includes: The second thin film stacked with the first thin film has an absolute value of LUMO energy level of 2.0 to 4.0 eV, and an absolute value of LUMO energy level of 4.5 to 7.0 eV.
9. The composite film according to claim 8, characterized in that The material of the second film includes: one or more of MoO3, ammonium molybdate, molybdenum ethoxide, phosphotungstic acid, phosphomolybdic acid, HATCN, NDP-9, F4TCNQ, F6TCNQ and CN6-CP; and / or, The thickness of the first thin film and the second thin film are respectively 5-100 nm.
10. A method for preparing a composite film according to any one of claims 1 to 9, characterized in that: include: providing a substrate; Disposing a first solution on the substrate to form a first liquid film; The first liquid film is subjected to a first annealing treatment to obtain a first thin film.
11. The method according to claim 10, characterized in that The first solution includes a first solvent and a first thin film material; the first thin film material includes a second functional material and a metal oxide and / or a metal oxide precursor; Wherein, the metal oxide comprises: one or more of zinc oxide, tin oxide, magnesium-doped zinc oxide and lithium-doped zinc oxide; and / or The metal oxide precursor comprises: one or more of zinc acetylacetonate, zinc acetate, lithium acetylacetonate, lithium acetate, magnesium acetylacetonate and magnesium acetate; and / or The temperature of the first annealing treatment is 100-200° C., and / or the time of the first annealing treatment is 5-60 minutes.
12. The method according to claim 11, characterized in that The first solvent includes: one or more of an alcohol solvent, an alcohol ether solvent or a ketone solvent; and / or, The alcohol solvent is one or more of n-butanol, n-pentanol, n-hexanol, and cyclohexanol; and / or, The alcohol ether solvent is one or more of ethylene glycol methyl ether, ethylene glycol dimethyl ether, ethylene glycol ethyl ether and ethylene glycol diethyl ether; and / or, The ketone solvent is one or more of cyclohexanone and 3-pentanone; and / or, The mass ratio of the first film material to the first solvent is (1-10):(99-90).
13. The method according to claim 10, characterized in that After obtaining the first film, the method further comprises: placing a second solution on the first film to form a second liquid film; performing a second annealing treatment on the second liquid film to obtain a second thin film; and / or The temperature of the second annealing treatment is 100-200° C., and / or the time of the second annealing treatment is 5-60 minutes.
14. The method according to claim 12, characterized in that The second solution includes a second solvent and a second film material; The second thin film material comprises: one or more of MoO3, ammonium molybdate, molybdenum ethoxide, phosphotungstic acid, phosphomolybdic acid, HATCN, NDP-9, F4TCNQ, F6TCNQ and CN6-CP; and / or The second solvent includes: one or more of an alcohol solvent, an alcohol ether solvent or a ketone solvent; and / or, The alcohol solvent is one or more of n-butanol, n-pentanol, n-hexanol, and cyclohexanol; and / or, The alcohol ether solvent is one or more of ethylene glycol methyl ether, ethylene glycol dimethyl ether, ethylene glycol ethyl ether and ethylene glycol diethyl ether; and / or, The ketone solvent is one or more of cyclohexanone and 3-pentanone; and / or, The mass ratio of the second film material to the second solvent is (1-10):(99-90).
15. A light emitting device, characterized in that: The invention comprises a first light-emitting unit, a composite film according to any one of claims 1 to 7 or a composite film prepared by the preparation method according to any one of claims 8 to 14, and a second light-emitting unit which are stacked in sequence.
16. The light emitting device according to claim 15, characterized in that: The light emitting device further comprises: a first electrode layer and a second electrode layer; The first light-emitting unit includes a first hole functional layer, a first light-emitting layer and a first electron functional layer; The second light-emitting unit includes a second hole functional layer, a second light-emitting layer, and a second electron functional layer; From bottom to top, the first electrode layer, the first hole functional layer, the first light-emitting layer, the first electron functional layer, the composite film, the second hole functional layer, the second light-emitting layer, the second electron functional layer and the second electrode layer are stacked in sequence.
17. The light emitting device according to claim 16, characterized in that: The composite film further comprises a second film; The first thin film is close to the first electron functional layer, and the second thin film of the composite thin film is close to the second hole functional layer.
18. The light emitting device according to claim 16, characterized in that: The materials of the first electrode layer and the second electrode layer are independently selected from one or more of metals, carbon materials and metal oxides, the metals include one or more of Al, Ag, Cu, Mo, Au, Ba, and Mg; the carbon materials include one or more of graphite, carbon nanotubes, graphene and carbon fibers; the metal oxides include doped or undoped metal oxides, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or include a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; And / or, the first hole functional layer and the second hole functional layer include a hole transport layer and / or a hole injection layer, and the materials of the hole transport layer and the hole injection layer are independently selected from one or more of TFB, PVK, poly-TPD, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, copper phthalocyanine, transition metal oxides and transition metal sulfur compounds, the transition metal oxides are selected from one or more of NiO, MoO2, WO3 and CuO, and the metal sulfur compounds are selected from one or more of MoS2, MoSe2, WS3, WSe3, CuS and CuSCN; And / or, the materials of the first light-emitting layer and the second light-emitting layer are independently selected from organic light-emitting materials or quantum dot light-emitting materials; The organic light-emitting material comprises: at least one of carbazole derivatives, triazine derivatives, oxazole derivatives, iridium-containing phosphorescent materials and platinum-containing phosphorescent materials; the quantum dot light-emitting material is selected from at least one of single-structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, the single-structure quantum dots are selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds, the II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSe At least one of Te, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe , at least one of PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe, and the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs s, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS;The perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, organic perovskite semiconductors or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs; + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2 + , Yb 2+ and Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic perovskite semiconductor is CMX3, wherein C is a carboxamidine group, M is a divalent metal cation, and M is selected from b 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ and Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - or I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH 3+ or [NH3(CH2) n NH3] 2+ , wherein n≥2, M is a divalent metal cation selected from b 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ and Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of; And / or, the first electronic functional layer and the second electronic functional layer include an electron injection layer and / or an electron transport layer, and the materials of the electron injection layer and the electron transport layer are independently selected from one or more of doped or undoped inorganic materials and organic materials; wherein the undoped inorganic material is selected from one or more of ZnO, TiO2, SnO2, Al2O3, GaO, Ga2O3, ZrO2, ZnS, ZnSe, CdS, BaTiO3, Cs2CO3 and Rb2CO3; the doped inorganic material includes the undoped inorganic material and a doping element, and the doping element is selected from one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti and Y; the organic material contained in the electron transport material is selected from one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds and hydroxyquinoline compounds.
19. A display panel comprising the light emitting device according to any one of claims 15 to 18.